GC-MS AND IR STUDIES OF ETHANOLIC EXTRACT OF COLONIAL ASCIDIAN- POLYCLINUM MADRASENSIS SEBASTIAN, 1952 - V.K. MEENAKSHI; C. VEERABAHU; K.F. ROSELIN (International Journal of Pharma and Bio Sciences, 2013)
Many marine origin organic molecules have entered clinical studies for their medicinal value. Ascidians, a marine sedentary urochordate has drawn the attention of researchers for its versatility as medicine and nutrition. Polyclinum madrasensis is a colonial ascidian found in abundance along Tuticorin coast. The ethanolic extract of Polyclinum madrasensis was subjected to GC-MS study to determine the possible bioactive components. The analysis revealed the presence of twenty two compounds. Chemical components which are biologically active include - n-Hexadecanoic acid, 4,8-dimethyl-Nonane-I-ol, 3-methyl- 1,2-Cyclopentane-diol, 1,2-diisooctyl ester of Benzenedicarboxylic acid, 1-Iodo-Tridecane, 2-butyl-octan-1-ol, Squalene, Cholesterol, Cholestan-3-ol, Dihydrotachysterol, 3-hydroxy-, (3á,17á)-Spiro[androst-5-ene-17,1'-cyclobutan]-2'-one and Diazoprogesterone. Major compounds are Cholesterol (23.01), Cholestan-3-ol (14.22), Squalene (10.50), n-Hexadecanoic acid (10.48) and Dihydrotachysterol (7.94). Of the twenty two compounds identified, thirteen compounds were reported for the first time from the ascidians of Indian water namely 4,8-dimethyl-Nonane-I-ol, (E)-5-Octadecene, 3-methyl-1,2-Cyclopentane-diol, 4,6,8-trimethyl-1-Nonane, Bis(2-ethylhexyl) ester of Hexanedioicacid, Methyl 2-hydroxydodecanoate, 1-Iodo-Tridecane, 2-butyl-octan-1-ol, (1,2-dimethylpropyl)-1-methyl-2-nonyl-cyclopropane, 6-methyl-octadecane, 2-oxo- methyl ester of Octadecanoic acid, Dihydrotachysterol and 1,8,15,22-Tricosatetrayne. These compounds exhibited many biological activities such as anticancer, antiarthritic, antiasthmatic, antimicrobial, antioxidant, antiandrogenic, pesticide and so on. Infrared (IR) spectral study of this species indicates the presence of primary free N-H stretching, alkanes –CH2- stretching, carboxylic acid and carbonyl compound.